Dihydrogoniothalamin, an Endothelium and NO-Dependent Vasodilator Drug Isolated from Aniba panurensis - Rezende, Bruno A.; Silva, Grazielle C.; Corradi, Rodrigo G.; Teles, Maria Madalena R. S.; Barbosa-Filho, José Maria; Lemos, Virginia S.; Cortes, Steyner F. (Planta Medica, 2015)
Dihydrogoniothalamin is a styrylpyrone isolated from the leaves of Aniba panurensis. The present work aimed at investigating the vasorelaxant activity of dihydrogoniothalamin and its underlying mechanism of action in the rat aorta. Dihydrogoniothalamin (0.01–100 µM) induced a concentration-dependent vasodilatation of aortas precontracted with phenylephrine. Endothelium removal or pretreatment of the preparation with NG nitro-L-arginine-methyl-ester abolished the vasodilator response for dihydrogoniothalamin. Pretreatment with calmidazolium did not affect the vasodilator response of dihydrogoniothalamin. On the other hand, wortmannin, a nonselective inhibitor of phosphatidylinositol 3-kinases, and protein kinase B inhibitor IV significantly shifted the concentration-response curve of dihydrogoniothalamin to the right and reduced its maximal effect. A nonselective antagonist of estrogen receptors, ICI 182,780, and a selective antagonist of estrogen receptor α, methyl-piperidino-pyrazole, were able to reduce the relaxation induced by dihydrogoniothalamin, but no effect was observed in the presence of the selective antagonists of estrogen receptor β and G protein-coupled receptor 30, 4-[2-phenyl-5,7-bis(trifluoromethyl)pyrazolo[1,5-a]pyrimidin-3-yl]phenol (PHTPP), and G-15, respectively. Dihydrogoniothalamin also increased the phosphorylation of the activation sites of endothelial nitric oxide synthase and protein kinase B. The present results led us to conclude that dihydrogoniothalamin is a vasodilator drug acting in an endothelium- and nitric oxide-dependent manner through a mechanism involving the activation of nitric oxide synthase via the phosphatidylinositol 3-kinase/protein kinase B pathway, partially by stimulation of estrogen receptor α.
Keywords: Aniba panurensis; Lauraceae; dihydrogoniothalamin; 6-styryl-2-pyrone; vasodilation; rat aorta